COOPERATIVE PRINCIPLES IN HOTMAN PARIS SHOW IN INEWS - Riska Utami Putri Damanik; I WY DIRGEYASA (TRANSFORM : Journal of English Language Teaching and Learning, 2019)
The purpose of this research is to find out the principle of cooperation that occurs at the Hotman Paris Show and the reason for the participants to violate the maxims. The method used by researchers in this study is qualitative research with data sourced from the Hotman Paris Show youtube account that uses #trending in the publishing process so that 17 videos are obtained. Data collection techniques using documentary techniques as data collection instruments. The analysis technique used is: 1) Identify the types of maxims and factors that violate the principle of cooperation that occurs at the Hotman Paris Show 2) Reducing irrelevant data sources with maxims and factors that violate the principle of cooperation 3) Classifying the data to its types 4) Interpreting the expressions of the principles of cooperation and factors that violate the principle of cooperation that occur in the conversations of the participants and 5) Drawing the conclusions based on the research problem of this study. The results of this research principle of cooperation on the maxim of quantity with the number of 65 utterances (64%), the maxim of quality with the number of 19 utterances (19%), the maxims of the relationship with the number of 8 utterances (8%) and manner with the number of 9 utterances (9 %). In the analysis of reasons, there were 83 errors made by participants which were divided into understatements of 20 data (24%), irony17 data (20%), overstatements 13 data (15%), extreme 10 data (12%), sarcasm 8 data (10%), ambiguous statements 7 data (8%), irrelevant statement 6 data (8%), and metaphors 3 data (4%).